Stepwise Synthesis of Tetra-imidazolium Macrocycles and Their N-Heterocyclic Carbene Metal Complexes - Li, Zili; Wiratpruk, Nuchareenat; Barnard, Peter J. (Frontiers in Chemistry, 2019)
A modular stepwise synthetic approach has been developed for the synthesis of tetra-imidazolium macrocycles. Initially a series of three bis(imidazolylmethyl)benzene precursors were alkylated with 1,2-dibromoethane to produce the corresponding bis-bromoethylimidazolium bromide salts. In the second step the bis-bromoethylimidazolium bromide salts were reacted with selected bis(imidazolylmethyl)benzene molecules to produce a series of two symmetrical and three asymmetrical tetra-imidazolium macrocycles. These tetra-imidazolium salts act receptors for anions and 1H-NMR titration studies were used to determine the association constants between two of the macrocycles and the halide anions chloride, bromide and iodide. The tetra-imidazolium salts are precursors for N-heterocyclic carbene (NHC) ligands and the corresponding silver(I), gold(I) and palladium(II) NHC complexes have been prepared. Varied structures were obtained, which depend on the chosen macrocyclic ligand and metal ion and in the case of the coinage metals Ag(I) and Au(I), mono, di and hexanuclear complexes were formed.